"Pain is forgotten where gain follows:" The masking effect of positive outcomes on emotional suffering. Issue 3 (23rd April 2018) - Sun, Hailong; Li, Aimei; Li, Bin; Wang, Haixia
Abstract : Previous research has shown that people tend to overstate or understate their past feelings in memory when asked to recall their past emotional experiences. Drawing from cognitive reappraisal theory and mood congruence theory, we presented an integrative explanation that the type of outcome of stressful events influences the magnitude and direction of bias in emotional memory. The results of two studies showed that individuals who succeeded in a postgraduate recruitment interview or a job interview tended to overstate positive emotions and understate negative emotions. In contrast, individuals who failed in an interview understated positive emotions and overstated negative emotions. This phenomenon can be named "pain is forgotten where gain follows." These results shed light on the controversy between mood congruent theory and the appraisal model as well as application values in intervention research on emotional biases.